A pilot randomized controlled trial of the iPeer2Peer program in adolescents with sickle cell disease: A mixed method study - Lauren Kelenc; Brittany Wiles; Fareha Nishat; Chitra Lalloo; Anya Nair; Craig Eling; Melanie Kirby-Allen; Ewurabena Simpson; Roona Sinha; Richard Ward; William T. Zempsky; Sara Ahola Kohut; et al. (Journal of Clinical and Translational Science)
Abstract